High-density potassium-sodium niobate-based piezoelectric ceramic and preparation method thereof

By doping boron oxide in KNN-based piezoelectric ceramics and adjusting the preparation process, the problem of low density of KNN-based ceramics is solved, and its density and piezoelectric properties are significantly improved.

CN119899031APending Publication Date: 2025-04-29ZHEJIANG UNIV +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411968477.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing KNN-based piezoelectric ceramics have low density, which affects its piezoelectric performance and device performance.

Method used

By doping boron oxide, the preparation process parameters of the ceramic are adjusted to improve the density of the ceramic.

Benefits of technology

The density, ferroelectric properties and piezoelectric properties of KNN piezoelectric ceramics have been significantly improved, and the maximum polarization strength and residual polarization strength have been improved, and the piezoelectric constant d33 reaches 118pC/N.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899031A_ABST
    Figure CN119899031A_ABST
Patent Text Reader

Abstract

The invention discloses a high-density potassium-sodium niobate-based piezoelectric ceramic, which is characterized in that the potassium-sodium niobate-based piezoelectric ceramic is K0. 48Na0. 52NbO3-xB2O3, and x is equal to 0.1-0.8. The invention also discloses a preparation method of the high-density potassium-sodium niobate-based piezoelectric ceramic. The invention also discloses a preparation method of the high-density potassium sodium niobate-based piezoelectric ceramic. The boron oxide is doped, so that the density of the KNN piezoelectric ceramic can be well improved, and the ferroelectric property and the piezoelectric property are also greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lead-free piezoelectric ceramics, and in particular to a high-density potassium sodium niobate-based piezoelectric ceramic and a preparation method thereof. Background Art

[0002] Piezoelectric ceramics have been widely used in devices such as brakes, sensors and transducers. They play an important role in the detection, conversion, processing and storage of various types of information and are an important component of high-tech materials. Perovskite-type lead zirconate titanate (PZT) piezoelectric ceramics are widely used in various fields, but the environmental pollution problem of its main component, lead oxide, has made the research of lead-free piezoelectric ceramics a hot topic. Among lead-free piezoelectric ceramics, potassium sodium niobate (KNN)-based lead-free piezoelectric ceramics have attracted much attention due to their relatively superior piezoelectric properties and higher Curie temperature. With the continuous deepening of modification work such as phase engineering and texture engineering, the piezoelectric constant (d 33 ) has exceeded 700pC / N, and has great application potential in many fields.

[0003] The performance of KNN is closely related to its density. Density not only affects the microstructure and electrical properties of the material, but also directly affects its mechanical strength and thermal stability. In the process of preparing KNN ceramics, reasonable control of density is crucial to obtain excellent piezoelectric properties. Studies have shown that appropriate density can improve the piezoelectric constant (d 33 ) and the planar electromechanical coupling coefficient (k P ), while reducing the porosity and defects of the material, thereby improving its performance. 2、 A lot of research has been done on the use of sintering aids such as Al2O3 and MgO to improve the sintering performance and electrical properties of KNN-based piezoelectric ceramics. For example, the Chinese patent with publication number CN116715522A discloses the introduction of a specific proportion of Fe in potassium sodium niobate-based piezoelectric ceramics. 3+ , making Fe 3+ Potassium sodium niobate-based piezoelectric ceramics that form defective dipoles in combination with oxygen vacancies can have a higher Curie temperature and good temperature stability; at the same time, the piezoelectric ceramics have a larger piezoelectric coupling constant kp and mechanical quality factor Qm, and can be used as a sintering aid to reduce the temperature of ordinary sintering and improve the density of the ceramic. And the Chinese patent with publication number CN110835266A discloses a potassium sodium niobate-based piezoelectric ceramic with the general formula K 0.48 Na 0.52 Sb 0.10 Nb 0.90-xMnO2, 0.2≤x≤0.8, x is the mass fraction; by adding a specific amount of manganese oxide as a sintering aid, the volatilization amount of Na2O and K2O during the sintering process is effectively reduced, so that the prepared potassium sodium niobate-based piezoelectric ceramics have good density.

[0004] At present, methods that significantly improve the density of KNN-based ceramics, such as hot pressing sintering and spark plasma sintering, have disadvantages such as high cost and complex operation. It can be seen that the preparation method of KNN-based ceramics needs to be further improved in order to improve the density and piezoelectric properties through simple and effective methods, and further optimize the device performance. Summary of the invention

[0005] The purpose of the present invention is to provide a high-density potassium sodium niobate-based piezoelectric ceramic and a preparation method thereof. By doping boron oxide, the density of the KNN piezoelectric ceramic can be improved, and the ferroelectric and piezoelectric properties are also greatly improved.

[0006] The present invention provides the following technical solutions:

[0007] A high-density potassium sodium niobate-based piezoelectric ceramic, wherein the potassium sodium niobate-based piezoelectric ceramic is K 0.48 Na 0.52 NbO3-xB2O3wt%, where x=0.1-0.8.

[0008] The potassium sodium niobate-based piezoelectric ceramic is K 0.48 Na 0.52 NbO3-xB2O3wt%, where x=0.3-0.8. It can more effectively improve the density of KNN piezoelectric ceramics.

[0009] The density of the potassium sodium niobate-based piezoelectric ceramic is 4.29-4.43 g / cm 3 .

[0010] The maximum polarization intensity of the potassium sodium niobate-based piezoelectric ceramic is 28.8-35 μC / cm 2 , the residual polarization intensity is 21.7-28.5μC / cm 2 , piezoelectric constant d 33 It is 108-118pC / N.

[0011] A method for preparing the above-mentioned high-density potassium sodium niobate-based piezoelectric ceramic, the preparation method comprising the following steps:

[0012] (1) mixing Na2CO3, K2CO3, B2O3 and Nb2O5 powders according to a stoichiometric ratio;

[0013] (2) placing the ingredients into a ball mill and milling them under the action of zirconium oxide balls and alcohol;

[0014] (3) drying the ball-milled slurry, sieving it, and calcining it to obtain potassium sodium niobate-based ceramic pre-sintered powder;

[0015] (4) ball-milling the pre-calcined powder and sieving it according to the method of steps (2) and (3), adding a binder and sieving it again;

[0016] (5) pre-pressing the sieved powder in step (4) into round tablets and then shaping them;

[0017] (6) calcining the formed disc to remove the binder, and then heating and sintering it into porcelain to obtain a potassium sodium niobate-based piezoelectric ceramic sheet;

[0018] (7) The prepared ceramic sheet is thinned to a certain thickness, a gold electrode is sputtered, and a voltage is applied for polarization.

[0019] Preferably, in step (6), after burning off the binder, the temperature is raised to 900°C at 5°C / min, and then raised to 1090-1120°C at 2°C / min to sinter into porcelain.

[0020] Preferably, in step (7), after burning off the binder, the sintered ceramic is thinned to a thickness of 0.25-0.35 mm, and then gold is sprayed and polarized under an electric field.

[0021] Specifically, gold was sprayed on the front and back surfaces using an ion sputtering apparatus for 120 seconds, and polarized for 30 minutes under an electric field of 30 kV / cm.

[0022] Preferably, the preparation method comprises:

[0023] (1) Na2CO3, K2CO3, B2O3 and Nb2O5 powders were placed in an oven at 80°C for 48 hours, and the dried analytically pure Na2CO3, K2CO3, B2O3 and Nb2O5 powders were mixed according to the stoichiometric ratio (K 0.48 Na 0.52 NbO3-xB2O3wt%), wherein x=0.1-0.8;

[0024] (2) putting the ingredients into a ball mill, mixing the ingredients prepared in step (1) in a ratio of 2:2:1 with zirconium oxide balls and alcohol, and milling the mixture at a speed of 300 r / min for 12 hours;

[0025] (3) pouring the ball-milled slurry into an enamel tray and drying it at room temperature, sieving the dried powder with a 100-150 mesh nylon sieve, and then calcining it in a muffle furnace at 750-900° C. for 5 h to obtain potassium sodium niobate-based ceramic pre-sintered powder;

[0026] (4) ball-milling and sieving the pre-calcined powder again in the manner of step (2) and step (3), adding 8-12 wt % of PVA binder to the sieved powder, and sieving with a 100-mesh nylon sieve;

[0027] (5) Pre-pressing the sieved powder into a disc with a diameter of 10 mm and a thickness of 1-1.2 mm, and then pressing it at a pressure of 150-250 MPa for 2 minutes to form a disc;

[0028] (6) keeping the formed disc at 600-650° C. for 2 hours to burn off the PVA binder, keeping it at 1090-1120° C. for 6 hours to sinter it into porcelain, and then cooling it to room temperature with the furnace to obtain a potassium sodium niobate-based piezoelectric ceramic sheet;

[0029] (7) The prepared ceramic sheet is thinned to a certain thickness, a gold electrode is sputtered, and a voltage is applied for polarization.

[0030] The present invention further improves the density by regulating the process parameters of each step in the preparation process.

[0031] Preferably, in step (6), the temperature is raised to 900°C at 5°C / min, and then raised to 1090-1120°C at 2°C / min to form porcelain. More preferably, the temperature is raised to 1090-1100°C to form porcelain, and the density of the prepared potassium sodium niobate-based piezoelectric ceramic is the highest.

[0032] Compared with the prior art, the present invention has the following excellent effects:

[0033] The present invention can improve the density of KNN piezoelectric ceramics by doping boron oxide, and the ferroelectric and piezoelectric properties are also greatly improved: compared with undoped KNN piezoelectric ceramics, the density of KNN-based ceramics can be optimally increased from 4.23 g / cm by doping boron oxide. 3 Increased to 4.43g / cm 3 (4.7% higher than pure potassium sodium niobate ceramics); the maximum polarization intensity increased from 27.8μC / cm 2 Increased to 35μC / cm 2 ; The residual polarization intensity is from 20.7μC / cm 2 Increased to 28.5μC / cm 2 , piezoelectric constant d 33 It reaches 118pC / N (15.7% higher than pure potassium sodium niobate ceramics) and reduces the optimal sintering temperature from 1120°C to 1100°C.

[0034] The preparation method provided by the present invention can simply and efficiently improve the density of potassium sodium niobate-based piezoelectric ceramics, and the prepared potassium sodium niobate-based piezoelectric ceramics do not contain lead elements and are environmentally friendly materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The XRD spectra of potassium sodium niobate-based ceramic powders obtained in Comparative Example 1 and Examples 1 to 3 are shown;

[0036] Figure 2 This is a SEM photo of potassium sodium niobate-based piezoelectric ceramics obtained in Comparative Example 1 and Examples 1 to 3;

[0037] Figure 3 hysteresis loop spectra of potassium sodium niobate-based piezoelectric ceramics obtained in comparative example 1 and examples 1 to 3;

[0038] Figure 4 The ferroelectric and piezoelectric properties of potassium sodium niobate-based piezoelectric ceramics obtained in Example 1 and Examples 1 to 3 are compared. DETAILED DESCRIPTION

[0039] The technical solution of the present invention is further explained below in conjunction with specific embodiments.

[0040] Example 1

[0041] The purities of the raw materials used for sample preparation are: Na2CO3 (99.99%), K2CO3 (99.99%), B2O3 (99.99%) and Nb2O5 (99.99%), and the doping amount of B2O3 is 0.1wt%.

[0042] (1) The raw material powder was dried in an oven at 80°C for 48 hours. 0.48 Na 0.52 NbO3-0.1B2O3wt%), calculate the mass of each raw material required to prepare 30g potassium sodium niobate powder according to the stoichiometric ratio, and weigh it with an electronic balance;

[0043] (2) Put the prepared materials into the ball mill, press the zirconium oxide balls: Step 1 prepared materials: alcohol

[0044] The materials were mixed and ball-milled at a ratio of 2:2:1, the ball-milling speed was 300 r / min, and the ball-milling time was 12 h;

[0045] (3) pouring the ball-milled slurry into an enamel tray and drying it at room temperature, sieving the dried powder with a 120-mesh nylon sieve, and then calcining it in a muffle furnace at 850° C. for 5 h to obtain potassium sodium niobate-based ceramic pre-sintered powder;

[0046] (4) ball-milling and sieving the pre-calcined powder again in the manner of steps 2 and 3, adding 10 wt % of PVA binder to the sieved powder, and sieving with a 100-mesh nylon sieve;

[0047] (5) Pre-press the sieved powder into a disc with a diameter of 10 mm and a thickness of 1-1.2 mm, and then press it at a pressure of 200 MPa for 2 minutes to form a disc;

[0048] (6) The formed disc is kept at 600°C for 2 hours to burn off the PVA binder, and then the temperature is increased to 900°C at 5°C / min, and then the temperature is increased to 1110°C at 2°C / min, and the temperature is kept at 1110°C for 6 hours to sinter into porcelain, and then cooled to room temperature in the furnace to obtain pure potassium sodium niobate piezoelectric ceramics.

[0049] (7) The sintered ceramic was thinned to a thickness of 0.25-0.35 mm, and gold was sprayed on the front and back surfaces using an ion sputtering apparatus for 120 seconds, followed by analysis and testing.

[0050] The density of KNN ceramics doped with 0.1wt% B2O3 was improved to 4.29g / cm 3 The main crystal phase of the prepared potassium sodium niobate ceramics is an orthorhombic perovskite structure, and the Curie temperature is maintained at around 420°C. The hysteresis loop is good, and Ps and Pr are 28.8μC / cm 2 and 21.7μC / cm 2 , d 33 It is 108pC / N.

[0051] Example 2

[0052] The purities of the raw materials used for sample preparation are: Na2CO3 (99.99%), K2CO3 (99.99%), B2O3 (99.99%) and Nb2O5 (99.99%), and the doping amount of B2O3 is 0.3wt%.

[0053] (1) The raw material powder was dried in an oven at 80°C for 48 hours. 0.48 Na 0.52 NbO3-0.3B2O3wt%), calculate the mass of each raw material required to prepare 30g of potassium sodium niobate powder according to the stoichiometric ratio, and weigh it with an electronic balance;

[0054] (2) Put the prepared materials into the ball mill, press the zirconium oxide balls: Step 1 prepared materials: alcohol

[0055] The materials were mixed and ball-milled at a ratio of 2:2:1, the ball-milling speed was 300 r / min, and the ball-milling time was 12 h;

[0056] (3) pouring the ball-milled slurry into an enamel tray and drying it at room temperature, sieving the dried powder with a 120-mesh nylon sieve, and then calcining it in a muffle furnace at 850° C. for 5 h to obtain potassium sodium niobate-based ceramic pre-sintered powder;

[0057] (4) ball-milling and sieving the pre-calcined powder again in the manner of steps 2 and 3, adding 10 wt % of PVA binder to the sieved powder, and sieving with a 100-mesh nylon sieve;

[0058] (5) Pre-press the sieved powder into a disc with a diameter of 10 mm and a thickness of 1-1.2 mm, and then press it at a pressure of 200 MPa for 2 minutes to form a disc;

[0059] (6) The formed disc is kept at 600°C for 2 hours to burn off the PVA binder, and then the temperature is increased to 900°C at 5°C / min, and then the temperature is increased to 1100°C at 2°C / min. It is kept at 1100°C for 6 hours to sinter into porcelain, and then cooled to room temperature in the furnace to obtain pure potassium sodium niobate piezoelectric ceramics.

[0060] (7) The sintered ceramic was thinned to a thickness of 0.25-0.35 mm, and gold was sprayed on the front and back surfaces using an ion sputtering apparatus for 120 seconds, followed by analysis and testing.

[0061] The density of KNN ceramics doped with 0.3wt% B2O3 is significantly improved to 4.43g / cm 3 The main crystal phase of the prepared potassium sodium niobate ceramics is an orthorhombic perovskite structure, and the Curie temperature is maintained at around 420°C. The hysteresis loop is good, and Ps and Pr are 35μC / cm 2 and 28.5μC / cm 2 , d 33 It is 118pC / N.

[0062] The potassium sodium niobate-based piezoelectric ceramic prepared in this embodiment has a strain of 0.18% under an electric field of 30 kV / cm, and a strain of 0.48% under an electric field of 50 kV / cm.

[0063] Example 3

[0064] The purities of the raw materials used for sample preparation are: Na2CO3 (99.99%), K2CO3 (99.99%), B2O3 (99.99%) and Nb2O5 (99.99%), and the doping amount of B2O3 is 0.8wt%.

[0065] (1) The raw material powder was dried in an oven at 80°C for 48 hours. 0.48 Na 0.52 NbO3-0.8B2O3wt%), calculate the mass of each raw material required to prepare 30g potassium sodium niobate powder according to the stoichiometric ratio, and weigh it with an electronic balance;

[0066] (2) Put the prepared materials into the ball mill, press the zirconium oxide balls: Step 1 prepared materials: alcohol

[0067] The materials were mixed and ball-milled at a ratio of 2:2:1, the ball-milling speed was 300 r / min, and the ball-milling time was 12 h;

[0068] (3) pouring the ball-milled slurry into an enamel tray and drying it at room temperature, sieving the dried powder with a 120-mesh nylon sieve, and then calcining it in a muffle furnace at 850° C. for 5 h to obtain potassium sodium niobate-based ceramic pre-sintered powder;

[0069] (4) ball-milling and sieving the pre-calcined powder again in the manner of steps 2 and 3, adding 10 wt % of PVA binder to the sieved powder, and sieving with a 100-mesh nylon sieve;

[0070] (5) Pre-press the sieved powder into a disc with a diameter of 10 mm and a thickness of 1-1.2 mm, and then press it at a pressure of 200 MPa for 2 minutes to form a disc;

[0071] (6) The formed disc is kept at 600°C for 2 hours to burn off the PVA binder, and then the temperature is increased to 900°C at 5°C / min, and then the temperature is increased to 1090°C at 2°C / min, and kept at 1090°C for 6 hours to sinter into porcelain, and then cooled to room temperature in the furnace to obtain pure potassium sodium niobate piezoelectric ceramics.

[0072] (7) The sintered ceramic was thinned to a thickness of 0.25-0.35 mm, and gold was sprayed on the front and back surfaces using an ion sputtering apparatus for 120 seconds, followed by analysis and testing.

[0073] The density of KNN ceramics with a B2O3 doping content of 0.8wt% was measured to be improved, but it was lower than that of KNN ceramics with a B2O3 doping content of 0.3wt%, which was 4.35g / cm 3 The main crystal phase of the prepared potassium sodium niobate ceramics is an orthorhombic perovskite structure, and the Curie temperature is maintained at around 420°C. The hysteresis loop is good, and Ps and Pr are 30.2μC / cm 2 and 22.4μC / cm 2 , d 33 It is 111pC / N.

[0074] Comparative Example 1

[0075] The purity of the raw materials used for sample preparation are: Na2CO3 (99.99%), K2CO3 (99.99%) and Nb2O5 (99.99%), and the B2O3 doping amount is 0.

[0076] (1) The raw material powder was dried in an oven at 80°C for 48 hours. 0.48 Na 0.52 NbO3), calculate the mass of each raw material required to prepare 30g of potassium sodium niobate powder according to the stoichiometric ratio, and weigh it with an electronic balance;

[0077] (2) Put the prepared materials into the ball mill, press the zirconium oxide balls: Step 1 prepared materials: alcohol

[0078] The materials were mixed and ball-milled at a ratio of 2:2:1, the ball-milling speed was 300 r / min, and the ball-milling time was 12 h;

[0079] (3) pouring the ball-milled slurry into an enamel tray and drying it at room temperature, sieving the dried powder with a 120-mesh nylon sieve, and then calcining it in a muffle furnace at 850° C. for 5 h to obtain potassium sodium niobate-based ceramic pre-sintered powder;

[0080] (4) ball-milling and sieving the pre-calcined powder again in the manner of steps 2 and 3, adding 10 wt % of PVA binder to the sieved powder, and sieving with a 100-mesh nylon sieve;

[0081] (5) Pre-press the sieved powder into a disc with a diameter of 10 mm and a thickness of 1-1.2 mm, and then press it at a pressure of 200 MPa for 2 minutes to form a disc;

[0082] (6) The formed disc is kept at 600°C for 2 hours to burn off the PVA binder, and then the temperature is increased to 900°C at 5°C / min, and then the temperature is increased to 1120°C at 2°C / min, and kept at 1120°C for 6 hours to sinter into porcelain, and then cooled to room temperature in the furnace to obtain pure potassium sodium niobate piezoelectric ceramics.

[0083] (7) The sintered ceramic was thinned to a thickness of 0.25-0.35 mm, and gold was sprayed on the front and back surfaces using an ion sputtering apparatus for 120 seconds, followed by analysis and testing.

[0084] According to the measurement, the density of pure potassium sodium niobate ceramic is relatively low, which is 4.23g / cm 3 The main crystal phase of the prepared potassium sodium niobate ceramics is an orthorhombic perovskite structure with a Curie temperature of 420°C. The hysteresis loop is good, with Ps and Pr being 27.8μC / cm 2 and 20.7μC / cm 2 , d 33 It is 102pC / N.

[0085] It can be seen from Comparative Example 1 and Examples 1-3 that boron oxide doping increases the density of potassium sodium niobate-based ceramics. The maximum polarization and residual polarization of KNN ceramics doped with boron oxide are increased, and the piezoelectric properties are improved. The sensitivity and efficiency of KNN-based piezoelectric ceramics in devices are enhanced, making related products of KNN ceramics more competitive in the market.

[0086] Figure 1 This is the X-ray diffraction diagram of the sample after sintering. It can be seen that all samples have a perovskite structure and there is no obvious difference in phase structure; Figure 2The scanning electron microscope images of the samples show that the average grain size of the KNN ceramics doped with boron oxide becomes larger and the density of the samples increases; Figure 3 This is the hysteresis loop of the sample for ferroelectric testing. The maximum polarization value of Example 2 is 35μC / cm 2 ; Figure 4 is the sample polarized d 33 Test data, d after boron oxide doping 33 Significantly improved, when the doping content is 0.3wt%, d 33 The increase of 15.7% compared with pure KNN ceramics shows that boron oxide doping can improve the piezoelectric properties of the sample.

Claims

1. A high-density potassium sodium niobate-based piezoelectric ceramic, characterized in that: The potassium sodium niobate-based piezoelectric ceramic is K 0.48 Na 0.52 NbO3-xB2O3wt%, where x=0.1-0.

8.

2. The high-density potassium sodium niobate-based piezoelectric ceramic according to claim 1, characterized in that: The potassium sodium niobate-based piezoelectric ceramic is K 0.48 Na 0.52 NbO3-xB2O3wt%, where x=0.3-0.

8.

3. The high-density potassium sodium niobate-based piezoelectric ceramic according to claim 1, characterized in that: The density of the potassium sodium niobate-based piezoelectric ceramic is 4.29-4.43 g / cm 3 .

4. The high-density potassium sodium niobate-based piezoelectric ceramic according to claim 1, characterized in that: The maximum polarization intensity of potassium sodium niobate-based piezoelectric ceramics is 28.8-35μC / cm 2 , the residual polarization intensity is 21.7-28.5μC / cm 2 , piezoelectric constant d 33 It is 108-118pC / N.

5. A method for preparing the high-density potassium sodium niobate-based piezoelectric ceramic according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: (1) mixing Na2CO3, K2CO3, B2O3 and Nb2O5 powders according to a stoichiometric ratio; (2) placing the ingredients into a ball mill and milling them under the action of zirconium oxide balls and alcohol; (3) drying the ball-milled slurry, sieving it, and calcining it to obtain potassium sodium niobate-based ceramic pre-sintered powder; (4) ball-milling the pre-calcined powder and sieving it according to the method of steps (2) and (3), adding a binder and sieving it again; (5) pre-pressing the sieved powder in step (4) into round tablets and then shaping them; (6) calcining the formed disc to remove the binder, and then heating and sintering it into porcelain to obtain a potassium sodium niobate-based piezoelectric ceramic sheet; (7) The prepared ceramic sheet is thinned to a certain thickness, a gold electrode is sputtered, and a voltage is applied for polarization.

6. The preparation method according to claim 5, characterized in that: In step (6), after the binder is burned off at 600-650°C, the temperature is first raised to 900°C and then raised to 1090-1120°C to sinter into porcelain.

7. The preparation method according to claim 6, characterized in that: The temperature is raised to 1090-1100℃ and sintered into porcelain.

8. The preparation method according to claim 5, characterized in that: In step (5), the thickness of the disc is 1-1.2 mm; in step (7), after burning off the binder, the thickness of the sintered ceramic is thinned to 0.25-0.35 mm, and after gold spraying, it is polarized under an electric field.

Citation Information

Patent Citations

  • Low-temperature sintered potassium sodium niobate lead-free piezoelectric ceramic and preparation method thereof

    CN102070337A

  • Additive for enhancing humidity stability of potassium sodium niobate-based leadless piezoelectric ceramics

    CN103693965A

  • Piezoelectric ceramic composition, its production method, piezoelectric element, and dielectric element

    JP2004244299A